Design and Construction of Modeling Tool of Linear Motion Experiment Assisted Toy Cars with Remote Control for Video Tracker Analysis - Hanifa Yoanda; - Asrizal; - Yohandri; - Yulkifli (Department of Physics – Universitas Negeri Padang UNP, 2023)
Physics has an important role in development and technology. Physics is concerned with experiment. From the results of research that has been carried out, it is known that there is no linear motion of kinematics experiment with speed control and the use of an inclined plane for the sliding plane of the linear motion experiment. The limitation of the instrument in displaying physical measurement quantities is one of the reasons. To overcome this limitation, a modeling tool assisted by a remote control toy car and analyze it using tracker software is created. The purpose of this study is to determine the performance specifications of the modeling tool for linear motion experiments assisted by a remote control toy car, determine the value of the accuracy and precision of the modeling tool, and also determine the correlation of physical quantities in linear motion experiments. Based on the results of data analysis using tracker software, there are three results can be explained. First, the performance specifications of linear motion experimental modeling tool with the length of the glide plane being 2 m and a width of 30 cm. The use of a dc motor, bluetooth module using an android connected to the HC-05. Second, the accuracy of the measurement of time and speed in the LMCV experiment was 98.4% and 97.2%. The accuracy values for the measurement of acceleration and velocity in the LMCA experiment were 95.53% and 95.5%. Third, in LMCV the correlation between position and time is in the form of a linear line, the correlation between velocity and time is in the form of a straight line with a constant value